Two hundred years of Say's law : essays on economic theory's most controversial principle - Kates, Steven, 1948- (Cheltenham, UK ; Northampton, MA : Edward Elgar Pub., 2003)
This work explores the validity of Jean-Baptiste Say's problematic principle, reminding readers that this 200-year debate has not yet been laid to rest. The book seeks to provide an understanding of the place of this principle in the minds of economists 200 years after it was first made explicit.
Includes bibliographical references and index.
oif 11/02/15
Loan
Keywords: Say, Jean Baptiste, -- 1767-1832.; Macroeconomics -- History; Say's law